The Effect of Job Satisfaction, Organizational Culture, and Perceived Organizational Support on Organizational Citizenship Behavior on Employee in Company: Pengaruh Kepuasan Kerja, Budaya Organisasi, dan Perceived Organizational Support terhadap Organizational Citizenship Behavior pada Karyawan Perusahaan - Aureliyah Putri, Ladynah Zarrah; Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of job satisfaction, organizational culture and perceptions of organizational support on organizational citizenship behavior in employees of PT. EMKL Transindra Perkasa Surabaya. This research is a quantitative research type. This research used a sample of 60 employees of PT. EMKL Transindra Perkasa Surabaya. This study uses multiple linear analysis as an analytical technique with the help of the SPSS (Statistical Program for Social Science) version 18.0 application. This study uses primary data and secondary data obtained from the company. Questionnaires are used in research as a tool for statistical testing. The results of the study prove that job satisfaction has an effect on OCB, organizational culture has an effect on OCB, perceptions of organizational support have an effect on OCB. And job satisfaction, organizational culture and perceived organizational support simultaneously affect OCB.